Group portrait of attendees Epworth League Institute at Humboldt - Gordon, John C., 1887-1967 (photographer):::Creator::::::::::::
Group portrait of the attendees of the August 1934 California Conference of the Epworth League Institute, held in Humboldt, California. Several conference members can be seen holding up signs denoting their local chapter's area, city, or county of origin.